2011
DOI: 10.2174/1874279301105010091
|View full text |Cite
|
Sign up to set email alerts
|

HIV Co-Testing Among Veterans with Chronic Hepatitis C in the Veterans Health Administration

Abstract: Objective: This retrospective study analyzed the testing rates of individuals enrolled in the Hepatitis C Clinical Case Registry for the Veterans Health Administration (VHA) in order to determine Human Immunodeficiency Virus (HIV) co-testing rates for veterans with hepatitis C (HCV). Design: A chart review of 247,006 veterans enrolled in the National HCV Clinical Case Registry was examined retrospectively. Regression analysis identified factors that increased the probability of being tested for HIV. Methods: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…The VHA has recommended HIV testing for all HCV-infected patients since 2003 [53]. In a retrospective study of veterans with HCV infection who underwent testing for HIV, 13.2% were found to have HIV infection [54]. A missed diagnosis of HIV infection may lead to misinformed treatment decisions and poorer outcomes for both HIV and HCV infections because dual infection alters management of both diseases.…”
Section: Screening and Diagnosismentioning
confidence: 99%
“…The VHA has recommended HIV testing for all HCV-infected patients since 2003 [53]. In a retrospective study of veterans with HCV infection who underwent testing for HIV, 13.2% were found to have HIV infection [54]. A missed diagnosis of HIV infection may lead to misinformed treatment decisions and poorer outcomes for both HIV and HCV infections because dual infection alters management of both diseases.…”
Section: Screening and Diagnosismentioning
confidence: 99%
“…8 On the other hand, HIV screening in HCV-positive patients among the Veterans Health Administration, Fuller et al demonstrated that only approximately one-third of veterans with HCV were tested for HIV (32%). 9 The ECDC review on hepatitis B and C collected available data in several specific populations. Among IDUs for example, the proportion of patients screened for HCV varied between 5% in the United Kingdom and 88% in Ireland.…”
mentioning
confidence: 99%
“…Use of alcohol among co-infected individuals adds an additional risk, with a 2001 meta-analysis indicating that the relative risk of decompensated liver disease or cirrhosis is 2.9 (95% confidence interval, 1.7-5.0) in co-infected individuals compared to individuals with HCV mono-infection [108]. The data demonstrates the need to simultaneously screen for HCV and HIV in order to identify, diagnose, and treat those with co-infections in order to maximize treatment outcomes [115]. The clinical health psychologist situated within infectious disease and liver clinics is in a unique position to inform, refer, and monitor co-infected patients, thus increasing collaboration across clinics and strengthening continuity of care.…”
Section: Hiv/hcv Co-infectionmentioning
confidence: 99%